SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MADRASAH IBTIDAIYAH MATHOLI’UL HUDA KELING JEPARA - Mohamad Susanto; Barowi Barowi; Moh Nasuka (Intelegensia : Jurnal Pendidikan Islam, 2020)
Abstract This study aims to find out the academic supervision of Madrasah Ibtidaiyah Head Madrasah Madoli in Kelep Jepara, teacher’s performance of Madrasah Ibtidaiyah Matholi'ul Huda Keling teachers in Jepara Regency, and the effectiveness of Madrasah Head supervision in improving Madrasah Ibtidaiyah Madrasah teachers' performance ul Huda Keling, Jepara Regency. This research is a type of field research using a qualitative approach with ethnographic research designs. The data collection using interview, observation, and documentation techniques. Before conducting the analysis, the data obtained was tested for validity by testing the validity and reliability through tests of credibility, transferability, depenability and confirmability. This research concludes: 1) Supervision of Madrasah Ibtidaiyah Matholi'ul Huda Keling Head of Jepara Regency is carried out in the form of a) giving guidance to teachers at madrasa meetings, b) enforcing discipline, and c) utilizing free time to discuss learning problems faced. . 2) Madrasa Ibtidaiyah Matholi'ul Huda Keling teacher performance in Jepara Regency has not shown good quality. In the aspect of preparing the Lesson Plan only as an administrative completeness. Teachers still using traditional method and most teachers do not use learning media. While in the aspect of the assessment system, they have shown seriousness in paying attention to the development of students in mastering the basic competencies taught. 3) Supervision conducted by the Head of MI Matholi'ul Huda Keling has not shown significant results in improving teacher performance because there is no planning, implementation, and evaluation specifically carried out for that purpose.Keywords: Teacher’s performance; Madrasa Ibtidaiyah; Academical Supervision